New insights into the process of peer review for EFL writing: A process-oriented socio-cultural perspective. (December 2018) - Zhao, Huahui
Abstract: The process of peer review for EFL writing has remained underexplored despite the increasing volume of research on peer review. The current study justified, adopted and substantiated a process-oriented approach to exploring peer review through the lens of the socio-cultural theory, after critiquing the predominant product-oriented research paradigm. Thirteen pairs of Chinese university EFL learners conducted peer review of six writing genres after receiving training in peer review. Peer interaction was scrutinised in terms of interaction patterns, mediating strategies, learning opportunities indicated by the amount and focus of oral peer feedback, and their intertwined relationships. Quantitative and qualitative analyses revealed three distinct interaction patterns and associated differed varieties of mediating strategies, amounts of oral peer feedback and focuses of peer interaction. The contrasting differences between the collaborative and dominant/dominant patterns revealed the importance of interactive peer interaction for generating a conducive learning environment for effective peer review for EFL writing. Important implications were provided based on results. Highlights: Distinct interaction patterns and mediating strategies were observed across dyads. Different mediating strategies and amounts and focuses of oral feedback were observed across three interaction patterns. Mutuality could substantially impact the patterns of peer interaction and reviewers' employment of mediating strategies. Collaborative interaction generated learning opportunities for reviewers and writers through negotiation and diversified mediating strategies. The frequency and quality of other regulation was intertwined, suggested by the reciprocal relationships between interaction and learning.